2017
DOI: 10.5194/isprs-archives-xlii-2-w3-559-2017
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral Photogrammetric Data Acquisition and Processing Forwall Paintings Studies

Abstract: ABSTRACT:In the field of wall paintings studies different imaging techniques are commonly used for the documentation and the decision making in term of conservation and restoration. There is nowadays some challenging issues to merge scientific imaging techniques in a multimodal context (i.e. multi-sensors, multi-dimensions, multi-spectral and multi-temporal approaches). For decades those CH objects has been widely documented with Technical Photography (TP) which gives precious information to understand or retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…• Extension of automatic GCP's extraction and coded targets support (Calvet et al, 2016) • Automatic orthophotomosaic generation, included multiband support (Pamart et al, 2017) The versatility and robustness of the iterative process allows currently the enrichment of the 3D scene by adding oriented pictures (even coming from a wide range of acquisition modalities). But at this stage of development, the spatially oriented resources are merged without generating or displacing other 3D coordinates to reduce internal process of AIOLI (computational costs of indexing and propagation steps).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…• Extension of automatic GCP's extraction and coded targets support (Calvet et al, 2016) • Automatic orthophotomosaic generation, included multiband support (Pamart et al, 2017) The versatility and robustness of the iterative process allows currently the enrichment of the 3D scene by adding oriented pictures (even coming from a wide range of acquisition modalities). But at this stage of development, the spatially oriented resources are merged without generating or displacing other 3D coordinates to reduce internal process of AIOLI (computational costs of indexing and propagation steps).…”
Section: Discussionmentioning
confidence: 99%
“…multisensor, multi-scalar, multi-spectral and/or simultaneously multitemporal). This article present the first implementation for automated processing of CH imaging multimodal acquisitions based on previous photogrammetric fusion experiments (Pamart et al, 2016, Pamart et al, 2017.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of high-resolution, easily operated digital cameras for NIR acquisition, in combination with SfM/MVS image-based modeling techniques, has made feasible the 3D spectral modeling for heritage applications. Contemporary research, which showed promising results [22][23][24][25][26][27][28], led us to the motivation for further experimentation.…”
Section: Near-infrared Imaging and Modelingmentioning
confidence: 99%
“…Eventually, selected sets of bands acquired by hyperspectral sensors may be also used in this way after the identification of most informative bandwidths [129], but still it is not a common approach. In contrast, combining different bands is a very frequent practice in case of technical photography, where false color photographs are intensively exploited [91,[130][131][132][133][134].…”
Section: Multispectral and Hyperspectral Imagingmentioning
confidence: 99%